2012
DOI: 10.1096/fj.12-218156
|View full text |Cite
|
Sign up to set email alerts
|

The prostamide‐related glaucoma therapy, bimatoprost, offers a novel approach for treating scalp alopecias

Abstract: Balding causes widespread psychological distress but is poorly controlled. The commonest treatment, minoxidil, was originally an antihypertensive drug that promoted unwanted hair. We hypothesized that another serendipitous discovery, increased eyelash growth side-effects of prostamide F2α-related eyedrops for glaucoma, may be relevant for scalp alopecias. Eyelash hairs and follicles are highly specialized and remain unaffected by androgens that inhibit scalp follicles and stimulate many others. Therefore, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 49 publications
(86 reference statements)
4
46
0
1
Order By: Relevance
“…Recently, Khidhir et al [16] demonstrated that the PG-related glaucoma drug bimatoprost can stimulate growth in non-eyelash hair follicles in mice in vivo and in human scalp hair follicles in dynamic organ culture, mirroring the stimulation of eyelashes known to occur in vivo. These strong similarities in responses by eyelash and scalp follicles contrast with their differing physiology [17], biological responses to androgens [18] and aging pigmentary changes [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Khidhir et al [16] demonstrated that the PG-related glaucoma drug bimatoprost can stimulate growth in non-eyelash hair follicles in mice in vivo and in human scalp hair follicles in dynamic organ culture, mirroring the stimulation of eyelashes known to occur in vivo. These strong similarities in responses by eyelash and scalp follicles contrast with their differing physiology [17], biological responses to androgens [18] and aging pigmentary changes [17].…”
Section: Discussionmentioning
confidence: 99%
“…These strong similarities in responses by eyelash and scalp follicles contrast with their differing physiology [17], biological responses to androgens [18] and aging pigmentary changes [17]. However, through studying the effects of bimatoprost and its antagonist in hair follicle organ culture, Khidhir et al [16] explained this dilemma by suggesting that the in vivo action of bimatoprost might be via direct effects on prostanoid receptors within the follicles themselves rather than indirect effects involving the vasculature or other surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…(D) Macroscopic images of hair follicles, either in control medium or FGF5 medium on days 0 through 8. In cultures containing FGF5, catagen entry, as determined by the shape of the end bulb (43), was earlier than in control cultures, explaining the observed reduction in growth rate.…”
Section: Methodsmentioning
confidence: 89%
“…A significant increase in the percentages of follicles in anagen phase was apparent, with a significant decrease in follicles in the telogen and late catagen phases (Tauchi et al, 2010). In recent studies, bimatoprost dose dependently prolonged anagen in human scalp follicles in vitro and stimulated the initiation of anagen of rodent pelage follicles in vivo Khidhir et al, 2013). As a pharmacological correlation, the prostamide receptor for bimatoprost was detected in the dermal papilla of human scalp follicles (Khidhir et al, 2013).…”
Section: B Hair Growthmentioning
confidence: 93%
“…In recent studies, bimatoprost dose dependently prolonged anagen in human scalp follicles in vitro and stimulated the initiation of anagen of rodent pelage follicles in vivo Khidhir et al, 2013). As a pharmacological correlation, the prostamide receptor for bimatoprost was detected in the dermal papilla of human scalp follicles (Khidhir et al, 2013). In mouse skin and blood, bimatoprost was found as an intact molecule not metabolized to the free acid 17-phenyl PGF 2a , indicating its stimulatory effect on hair growth is through interaction with prostamide receptors.…”
Section: B Hair Growthmentioning
confidence: 99%